(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The research investigates the domestic violence against women in TandoAllahyar District-Sindh Pakistan. Data were collected through survey from 200 respondents. Data were analyzed by using SPSS-21 version. It was revealed that most of the surveyed women were quiet depressed and their male counterparts not working but they are solely depending on women work in SMEs. It was further revealed that the rural women is less confident and their husbands were always given them hard time once they are exposing themselves to outside the boundaries of the house